Predicting Effects of Corrosion Erosion of High Strength Steel Pipelines Elbow on CO2-Acetic Acid (HAc) Solution - Asmara, Y. P.; M. F., Ismail; L., Giok Chui (IOP Publishing, 2016)

(untitled)
Simultaneously effect of erosion combined with corrosion becomes the most concern in oil and gas industries. It is due to the fast deterioration of metal as effects of solid particles mixed with corrosive environment. There are many corrosion software to investigate possible degradation mechanisms developed by researchers. They are using many combination factors of chemical reactions and physical process. However effects of CO2 and acid on pipelines orientations are still remain uncovered in their simulation. This research will investigate combination effects of CO2 and HAc on corrosion and erosion artificial environmental containing sands particles in 45°, 90° and 180° elbow pipelines. The research used theoretical calculations combined with experiments for verification. The main concerns are to investigate the maximum erosion corrosion rate and maximum shear stress at the surface. Methodology used to calculate corrosion rate are Linear Polarization Resistance (LPR) and weight loss. The results showed that at 45°, erosion rate is the more significant effects in contributing degradation of the metal. The effects of CO2 and HAc gave significant effects when flow rate of the solution are high which reflect synergism effects of solid particles and those chemical compositions.